Promoter hypermethylation of p16 and APC in gastrointestinal cancer patients - Erdem, Beril; Küçükyıldırım, Sibel; Sağlar, Emel; Polat, Zülfikar; Mergen, Hatice (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Cancer is a consequence of the disruption of cellular regulation. Epigenetic is one of the reasons of this disruption. Epigenetic factors play a role in the carcinogenesis by affecting proto-oncogenes and tumor suppressor genes and it is one of the most popular research areas in recent years. DNA methylation, which is an epigenetic mechanism, occurs in the early stages of tumorigenesis. Promoter methylation which causes the silence of tumor suppressor genes have been studied extensively in various tumor types. The aim of this study was to investigate promoter methylation of certain tumor suppressor genes, Cyclin-dependent kinase inhibitor 2A (p16) and Adenomatous polyposis coli (APC), which take part in gastrointestinal tumorigenesis. Materials and Methods: To detect the promoter methylation of p16 and APC genes, tissue samples from 20 gastrointestinal cancer patients and peripheral blood samples from 15 healthy individuals were collected for Methylation-Specific Polymerase Chain Reaction (MSP) analysis. Results: According to the statistical analysis, in tumor tissue, positive methylation ratio of p16 and APC genes was found respectively 30% (6/20) and 50% (10/20). The difference of promoter methylation of these genes between tumor tissues and control group was significantly observed (p=0.02 and 0.001, respectively). An alteration of promoter methylation of APC gene according to tumor localization was found (p=0.007), but there was no significant difference observed in p16. Conclusion: In our study, promoter methylation which was considered to be occurred as an early event in gastrointestinal carcinogenesis was observed in p16 and APC genes.